2016
DOI: 10.5935/0103-507x.20160045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the five-year operation period of a rapid response team led by an intensive care physician at a university hospital

Abstract: ObjectiveTo evaluate the implementation of a multidisciplinary rapid response team led by an intensive care physician at a university hospital.MethodsThis retrospective cohort study analyzed assessment forms that were completed during the assessments made by the rapid response team of a university hospital between March 2009 and February 2014.ResultsData were collected from 1,628 assessments performed by the rapid response team for 1,024 patients and included 1,423 code yellow events and 205 code blue events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
36

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 22 publications
0
9
0
36
Order By: Relevance
“…(6-11) A more unfavorable economic context is likely to affect necessary investments in acquiring equipment and hiring staff. (6,9) More hierarchical professional relations and cultural norms may constitute barriers to teamwork, a fundamental attribute of the intervention. (12,13) Additionally, in these countries, healthcare monitoring is uncommon with data collection seen as a costly and time-consuming task by frontline professionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6-11) A more unfavorable economic context is likely to affect necessary investments in acquiring equipment and hiring staff. (6,9) More hierarchical professional relations and cultural norms may constitute barriers to teamwork, a fundamental attribute of the intervention. (12,13) Additionally, in these countries, healthcare monitoring is uncommon with data collection seen as a costly and time-consuming task by frontline professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of RRTs in Latin American countries, for example, may be especially relevant considering the scarcity of intensive care unit (ICU) beds in the face of systemic financial, structural and political problems, (6,9,14,15) which contrasts to ICU overcrowding in developed countries generally associated with population aging. (16,17) While in studies conducted in England, (18) France, (19) and Hong Kong, (20) estimates of late ICU admissions are 32.6%, 37.6% and 37.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…( 7 ) It is estimated that patients who have cardiac arrests generally present with symptoms or clinical signs that predict the occurrence six to eight hours before the event. ( 5 ) The most common signs of cardiac arrest among 66% of examined patients are desaturation and hypotension, findings that were verified in several studies conducted in hospitals with different conditions and structures. ( 7 - 10 )…”
Section: Introductionmentioning
confidence: 69%
“…Some previous studies have reported on the implementation of RRTs in Brazil. ( 5 , 43 , 45 , 46 ) A large private tertiary hospital in São Paulo that instituted an RRT in 2005 evaluated the impact of this implementation. That study demonstrated that RRT implementation was associated with a significant reduction in the rates of cardiorespiratory arrest (from 3.54 to 1.69 per 1,000 discharges) and in-hospital mortality (16.27 to 14.34 deaths per 1,000 discharges).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation